[Book Review] Teaching the History of the Book, edited by Matteo Pangallo and Emily B. Todd - David Lemmons (Teaching & Learning Inquiry: The ISSOTL Journal, 2023)
Book review of Teaching the History of the Book, edited by Matteo Pangallo and Emily B. Todd.